CARRAGEENAN INDUCES CELL DEATH IN RATS BLOOD - Kopanytsia, O. M.; Marushchak, M. I.; Krynytska, I. Ya. (International Journal of Medicine and Medical Research, 2018)
Background. Because of its physical and chemical properties, carrageenan is fairly widely used. About 70 % of the carrageenan produced in the world is used in the food industry. Previous studies point to the development of oxidative stress in rats, by means of which carrageenan chronic enterocolitis was modeled. Objective. The aim of our study was to investigate the level of apoptosis and necrosis in the suspension of leukocytes in rats using 0.5 % and 1.0 % solutions of carrageenan. Methods. Annexin V (V) binding assays were performed using Annexin V Apoptosis Kit (Sigma Aldrich, USA), caspase rate in leukocyte-lymphocyte blood fractions was determined by spectrofotometry. Results. It was established that in the experimental application of carrageenan, the percentage of leukocytes with signs of apoptosis in both experimental groups statistically significantly increased. It was detected by the increased activity of effector caspase-3 in 1 month after the experiment in 1.5 times in the 2nd group and in 2.8 times in the 3rd group vs control data that point to caspase-dependent apoptotic pathway in case of carrageenan usage in rats. Conclusions. Oral use of carrageenan in rats was accompanied by the increase in the number of leukocytes with signs of apoptosis. The animals that consumed 1.0 % solution of carrageenan had more obvious increase in the activity of caspase-3 in serum relative to a group of rats consuming 0.5 % of carrageenan, proving the increase in the severity of apoptotic processes in intestine with the increase of the dose of carrageenan.